EVALUATION OF THE IN VITRO ANTIOXIDANT AND ANTIBACTERIAL ACTIVITIES OF SECONDARY METABOLITES PRODUCED FROM LICHENS - Mastan, A.; B.SREEDEVI; Kumari, J.Pramoda (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Lichens produce a great variety of secondary metabolites and most of them are unique. These chemically diverse lichen substances accumulate on the outer surfaces of the hyphae. Living cells may generate free radicals and other reactive oxygen species by-products as a results of physiological and biochemical processes. In the present study, the lichens Cladomia fimbriata, Permilopsis ambigua, Punctelia subrudecta, Evernia mesomorpha secondary metabolites were extracted in the two solvents methanol and water. The antimicrobial efficacy of extracted lichen compounds tested against bacteria.Total phenolic contents of the aqueous extracts of the plants were determined by the Folin-Ciocalteus reagent method. Proteins, carbohydrates, phenols, tannins, flavonoids, saponins, were detected in all of the lichens tested. The highest antibacterial activity was observed in sample C against Bacillus (1.9cm) in methanol extracts. The more total phenolic concentration was observed in methanol extract of P. subrudecta and followed by P. ambigua. The absorbance values of water extract extracted from P. subrudecta, sample-C (74.61±2.14) shows significantly higher values than the methanolic extract of P. subrudecta and followed by sample B, D and A respectively. The lichen extracts showed comparable and strong antioxidant activity, exhibited higher DPPH and hydroxyl radical scavenging activity. Among the tested lichen extracts, water extract of sample D (Evernia mesomorpha) gave highest reducing power, although the reducing activity was lower than the standard ascorbic acid. Our findings provided evidence that crude aqueous and organic solvent extracts of lichens contain medicinally important bioactive compounds and it justifies their use in the traditional medicine. Keywords: Secondary metabolites, antibacterial, antioxidant activity, phytochemicals, zone of inhibition.